Soft X-ray laser diagnostics of exploding aluminum wire plasmas - Rocca, Jorge J., author; Marconi, M. C., author; Filevich, J., author; Jankowska, E., author; Szapiro, B., author; Hammarsten, E. C., author; Springer-Verlag, publisher (Colorado State University. Libraries, 2004)
The evolution of current-driven thin single Al wire plasmas was studied with soft X-ray shadowgraphy and interferometry using a very compact capillary discharge-driven λ = 46.9 nm laser probe. Wires of 25 μm diameter excited by current pulses with a 78 A/ns increase rate were observed to expand uniformly at a rate of 3.5 μm/ns. In contrast, an increase in the rate of energy deposited per unit mass was observed to give rise to significant early plasma instabilities. The results illustrate the use of table-top soft X-ray lasers as a new tool for the diagnostics of dense pulse power driven plasmas.